(untitled) (Research, Society and Development, 2020)
The Alouatta belzebul is a species classified as "Vulnerable" and this is mainly justified by the hunting, fragmentation and loss of habitat in tropical forests. The anatomy of this genus presents peculiar characteristics in all the studied species, so this work aimed to describe the morphology of the digestive tube of Alouatta belzebul in order to provide subsidies for evaluation of diets, clinical and surgical procedures in these animals. Ten adult Alouatta belzebul specimens of different ages were used. The study was carried in the Federal University of Goiás and approved in the ethics committee n. 083/17. The previously cryopreserved animals were thawed and fixed by intramuscular and intracavitary infusion of 10% aqueous follicle solution. There are several variations in the macroscopic anatomy of the digestive tube between the primates and these variations occur according to the eating habits. In Alouatta belzebul, which are folivore-frugivorous, the digestive tract covers most of the abdominal cavity. These animals have variable numbers of palatal ridges, from 10 to 17 pairs of crests, regardless of sex and age, values ​​different from those reported for Sapajus libidinosus, from 18 to 21 pairs of crests. The pseudo-compartmentalized stomach with one glandular region and two aglandular, resembling the findings of Nasalis larvatus. The large intestine presents the enlarged cecum in L-shaped, corroborating with the findings in Callithrix penicillata The results demonstrate that the structural variations of the digestive tube occur according to the dietary habits of the different species.